2019
DOI: 10.1021/acscatal.9b01087
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide-Catalyzed Stereoselective Cyanation Reaction

Abstract: We report a Michael-type cyanation reaction of coumarins by using CO2 as a catalyst. The delivery of the nucleophilic cyanide was realized by catalytic amounts of CO2, which forms cyanoformate and bicarbonate in the presence of water. Under ambient conditions, CO2-catalyzed reactions afforded high chemo- and diastereoselectivity of β-nitrile carbonyls, whereas only low reactivities were observed under argon or N2. Computational and experimental data suggest the catalytic role of CO2, which functions as a Lewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…However, it is important to note that the employment of CO 2 can complicate the outcome of reactions due to undesired binding of nucleophiles therefore reducing the reactivity. Based on our investigation and previous studies [15,27,28], we presumed that the positive effects of CO 2 in catalyzing chemical reactions can be general, particularly in reactions involving reversible steps. In the current investigation with chalcones, the reaction is highly controlled by thermodynamics that allowed us to access various products in high yield.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, it is important to note that the employment of CO 2 can complicate the outcome of reactions due to undesired binding of nucleophiles therefore reducing the reactivity. Based on our investigation and previous studies [15,27,28], we presumed that the positive effects of CO 2 in catalyzing chemical reactions can be general, particularly in reactions involving reversible steps. In the current investigation with chalcones, the reaction is highly controlled by thermodynamics that allowed us to access various products in high yield.…”
Section: Discussionmentioning
confidence: 72%
“…The use of solid metal cyanide sources is desirable to avoid volatile HCN, however, it often requires high reaction temperature due to the low solubility and reactivity of alkali metal cyanides [14]. Recently our group demonstrated the employment of catalytic amounts of CO 2 for 1,4-conjugate cyanide addition reaction of coumarin substrates [15]. The use of ammonium cyanide as a nucleophile was sufficient to quantitatively convert the starting materials to the desired products under 1 atm of CO 2 (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Recent applications of carbon dioxide in organic synthesis showed fruitful success particularly in CO 2 ‐incorporation, [5] CO 2 as a temporal protecting group for C−H activation, [6] CO 2 for asymmetric catalysis [7] and oxidation reactions [8] . We recently investigated the role of CO 2 in a cyanation reaction, [9] where CO 2 can be used in catalytic amounts to facilitate the stereoselective transformation of activated electrophiles via 1,4‐conjugate addition reactions. Cyanohydrin synthesis −1,2‐cyanide addition reactions to carbonyls—is one of the oldest C−C bond‐forming reactions using HCN as a cyanide source [10] .…”
Section: Methodsmentioning
confidence: 99%
“…Although NaBH(OCHO) 3 is a congener of NaBH(OAc) 3 , the use of NaBH(OCHO) 3 as a reducing agent for reductive amination has to the best of our knowledge not yet been reported. Our on‐going research program to utilize CO 2 for controlling organic reactions [ 17 ] showed promising reactivity patterns in developing new chemical reactivity of nucleophiles while improving (stereo)selectivity. Although, the reactivity and selectivity of NaBH 4 can conveniently be modified through the addition of reagents or Lewis acidic metals to NaBH 4 , CO 2 has been overlooked for this purpose.…”
Section: Introductionmentioning
confidence: 99%